2021
DOI: 10.1080/21655979.2021.1946633
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Astragalus Membranaceus on osteoporosis in SAMP6 mice by regulating vitaminD/FGF23/Klotho signaling pathway

Abstract: Spontaneous senile osteoporosis severely threatens the health of the senior population which has emerged as a severe issue for society. A SAMP6 mouse model was utilized to estimate the impact of intragastrically administered Astragalus Membranaceus (AR) on spontaneous senile osteoporosis. Bone mineral density (BMD) and bone microstructure were measured using Micro-CT; contents of calcium and phosphorus were determined with the colorimetric method; and gene and protein expressions of fibroblast growth factor 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…5 6 7 Researches have found that certain components in Huangqi (Radix Astragali) can promote the formation of osteoblasts, delay osteoporosis, and may be beneficial for senile osteoporosis. 8 It has also confirmed that astragaloside IV in Huangqi (Radix Astragali) can promote the differentiation of bone marrow–derived mesenchymal stem cells which may provide new ideas for the treatment of osteoporosis. 9 At present, studies have also verified that Huangqi (Radix Astragali) has the effects of antioxidant, anti-inflammatory, analgesic, anticancer, thrombosis preventing, hypoglycemic, lipid regulating, immune regulating, and antiaging.…”
Section: Huangqi Guizhi Wuwu Decoctionmentioning
confidence: 90%
“…5 6 7 Researches have found that certain components in Huangqi (Radix Astragali) can promote the formation of osteoblasts, delay osteoporosis, and may be beneficial for senile osteoporosis. 8 It has also confirmed that astragaloside IV in Huangqi (Radix Astragali) can promote the differentiation of bone marrow–derived mesenchymal stem cells which may provide new ideas for the treatment of osteoporosis. 9 At present, studies have also verified that Huangqi (Radix Astragali) has the effects of antioxidant, anti-inflammatory, analgesic, anticancer, thrombosis preventing, hypoglycemic, lipid regulating, immune regulating, and antiaging.…”
Section: Huangqi Guizhi Wuwu Decoctionmentioning
confidence: 90%
“…Substrates I and II were added to the sample and mixed well, and a termination solution was added and mixed well. The sample was detected by enzyme labeling at 450 nm wavelength [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bge. 14 The main components of AM are saponins, polysaccharides, and flavonoids, which have a variety of biological functions such as immune regulation, antitumor, antivirus, antiaging, and hypoglycemic. 15 In the treatment of SLE, AM could increase the curative effect, reduce the side effects of glucocorticoid and reduce the infection through multiple ways of immunomodulation.…”
Section: Introductionmentioning
confidence: 99%
“…Hsiao and AM (Fisch.) Bge 14 . The main components of AM are saponins, polysaccharides, and flavonoids, which have a variety of biological functions such as immune regulation, antitumor, antivirus, antiaging, and hypoglycemic 15 .…”
Section: Introductionmentioning
confidence: 99%